2015
DOI: 10.1038/srep11415
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative assessment of single-cell whole genome amplification methods for detecting copy number variation using hippocampal neurons

Abstract: Single-cell genomic analysis has grown rapidly in recent years and finds widespread applications in various fields of biology, including cancer biology, development, immunology, pre-implantation genetic diagnosis, and neurobiology. To date, the amplification bias, amplification uniformity and reproducibility of the three major single cell whole genome amplification methods (GenomePlex WGA4, MDA and MALBAC) have not been systematically investigated using mammalian cells. In this study, we amplified genomic DNA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
57
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(59 citation statements)
references
References 38 publications
(63 reference statements)
2
57
0
Order By: Relevance
“…Other valve-based studies have collectively demonstrated the utility of this approach for performing whole or targeted genome studies in single cells 5356 . Although current methods are achieving ever more efficient cover age and uniformity, further improvements can still be made to enable truly genome-wide profiling, reduce amplification errors and allow more-confident calling of copy-number variants (CNVs) and single-nucleotide variants (SNVs) 26,57,58 .…”
Section: Microfluidic Devices For the Omicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Other valve-based studies have collectively demonstrated the utility of this approach for performing whole or targeted genome studies in single cells 5356 . Although current methods are achieving ever more efficient cover age and uniformity, further improvements can still be made to enable truly genome-wide profiling, reduce amplification errors and allow more-confident calling of copy-number variants (CNVs) and single-nucleotide variants (SNVs) 26,57,58 .…”
Section: Microfluidic Devices For the Omicsmentioning
confidence: 99%
“…By comparison, proteins, for which consistent and universal probes (typically antibodies) are unavailable, show, on average, higher expression levels than their cognate mRNAs 100 , greater stability 56 and buffering from transcriptional noise 57 . These considerations, coupled with a potentially more direct role in cellular behaviour 27 and the feasibility of non-destructive detection (for secreted and cell-surface-bound factors), have often made protein expression the de facto cellular characteristic.…”
Section: Microfluidic Devices For the Omicsmentioning
confidence: 99%
“…There are plenty of commercial WGA kits and different kits are based on different strategies: multiple displacement amplification (MDA), degenerate-oligonucleotide-primed PCR (DOP-PCR), and multiple annealing and looping-based amplification cycles (MALBAC, MALBAC-like) are three major WGA strategies. Different strategy may cause different WGA performance and some studies have paid efforts in the comparison of WGA methods [15][16][17][18][19]. However, current related researches are conducted on Illumina sequencing platforms, the results have not validated on Ion Proton platform.…”
Section: Introductionmentioning
confidence: 99%
“…A second approach, degenerate oligonucleotide priming PCR (DOP-PCR), involves the fragmentation of the genome into small pieces, followed by amplification with random priming 117 . This method amplifies the genome more evenly than MDA, and is thus particularly well-suited to studying copy-number variation 14,85,86,118 . Hybrid methods, including multiple annealing and looping-based amplification cycles (MALBAC) and PicoPlex, include pre-amplification with a tagged primer.…”
Section: Retrospective Methods Of Lineage Tracingmentioning
confidence: 99%
“…MALBAC-based amplification is more even across the genome than MDA-based amplification, but error rates are higher 72 . With this more even amplification, hybrid methods are appropriate for investigating CNVs 118 , structural variants 120 and retrotransposition events 79 , although chimeric amplification products that occur in the MALBAC and MDA reactions are of particular concern for interpreting retrotransposition events and structural variants 80 .…”
Section: Retrospective Methods Of Lineage Tracingmentioning
confidence: 99%